2014
DOI: 10.1186/bcr3605
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations in breast cancer: reconciling findings from preclinical and clinical data

Abstract: PIK3CA mutations represent one of the most common genetic aberrations in breast cancer. They have been reported to be present in over one-third of cases, with enrichment in the luminal and in human epidermal growth factor receptor 2-positive subtypes. Substantial preclinical data on the oncogenic properties of these mutations have been reported. However, whilst the preclinical data have clearly shown an association with robust activation of the pathway and resistance to common therapies used in breast cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 78 publications
5
64
1
2
Order By: Relevance
“…These results support recommendations of using these two makers, beside ER, PR and HER2 negativity, as additional surrogates in characterising breast cancers with basal phenotype [25]. Moreover, the roles played by PIK3CA in BC progression through its downstream effectors, especially through driving an epithelial-to-mesenchymal transition program (EMT) with up regulation of N-cadherin and P-cadherin has been reported in the same series [26,27], as well as in others [28].…”
Section: Discussionsupporting
confidence: 84%
“…These results support recommendations of using these two makers, beside ER, PR and HER2 negativity, as additional surrogates in characterising breast cancers with basal phenotype [25]. Moreover, the roles played by PIK3CA in BC progression through its downstream effectors, especially through driving an epithelial-to-mesenchymal transition program (EMT) with up regulation of N-cadherin and P-cadherin has been reported in the same series [26,27], as well as in others [28].…”
Section: Discussionsupporting
confidence: 84%
“…PIK3CA mutations represent one of the most common genetic aberrations in breast cancer [68]. In a study on 241 patients with breast cancer, PIK3CA mutations were found in 15.8% cases [69].…”
Section: Leptin Biology and Molecules Of Relevant Signal Transductmentioning
confidence: 99%
“…PI3K signaling is upregulated in an estimated 70% of breast cancers (Leroy et al 2016), whether as a consequence of increased IGF1R (or EGFR) pathway activation, or secondary to oncogenic mutations in PIK3CA, reported to occur in about 25% of all breast cancers (Zardavas et al 2014). IGF1R pathway activation is known to confer resistance to PI3K inhibition (Leroy et al 2016), suggesting the possible utility of combined IGF1R/PI3K inhibition.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%